Best practice of framing and communicating school goals among principals of cluster secondary schools towards realization of Malaysian education blueprint 2013-2025 - Salleh, Mohamad Johdi (International Journal of Humanities and Social Science Invention, 2014)
The study aims to examine the best practice of framing and communicating school goals among principals of cluster secondary schools Malaysia according to principals and teachers perceptions. The Principal Instructional Management Rating Scale (PIMRS) modified by Hallinger and Murphy (1985), Latip (2006), and, Hatta (2010) was used as the data collection instrument through survey questionnaire. There were 871 respondents of different genders, ethnics, type of schools, and, position of responsibilities at schools were participated. The result of the study shows that three highest score were respectively on items ‘Discuss the school's academic goals with teachers at faculty meetings’ mean 4.25, ‘Communicate the school's academic goals to people at school’ mean 4.24, and, ‘Refer to the school's goals in student assemblies’ mean 4.21. It is hoped that this research will provide useful findings which will effectively assist the process of instructional leadership enhancement among principals and teachers of cluster secondary schools in order to improve students' academic performance in achieving the first class human capital who are compatibly excellent nationally and internationally towards realization of the Malaysian Education Blueprint 2013-2025.